Development of ozone generation system in the production of Olive oil ointment [electronic resource] - 238138 Hassan Kosnan; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007